Controlled synthesis of barium chromate microcrystals. Issue 11 (21st October 2014) - Xiao, H.; Ding, S.S.; Xu, X.; Pan, N.; Fan, D.Y.; Yang, H.J.; Lei, M.; Du, Y.X.; Zhang, R.; Wang, Y.G.; Tang, W.H.
<x xml:space="preserve">Abstract</x> BaCrO4 microcrystals with various morphologies were synthesized using poly (sodium 4‐styrenesulfonate) (PSSS) as template agent. It is found that pH values and concentrations of reactants and PSS are important parameters in the morphology and size evolution of BaCrO4. PSS can complexes Ba2+ first, then affects the nucleation and crystallization process by interacting with the face of crystal. In addition, the possible mechanism of photoluminescence (PL) spectra was also proposed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>